Problematika penggunaan hisab rukyat dalam penetapan awal bulan Qamariah - Sirojuttholibin, Muhamad (Maliki Interdisciplinary Journal, 2024)
The issue of determining the beginning of the qamariah month in Islam is very important. Because it is also related to the prerequisites for the validity of worship such as Ramadan fasting and the implementation of the Hajj. When the results of ijtihad fall on the same day, it does not cause problems in society, but when the results fall on different days, it is possible to cause problems. The difference in the results of ijtihad is because it uses two different methods, namely hisab, rukyat. The two methods also have different provisions and criteria to decide when the month is starting falls. So that it raises various opinions, arguments, and theories. The government has implemented all kinds of ways to solve this problem. However, the use of hisab and rukyat methods is difficult to unite, because they have different criteria. But with these differences, we should still respect each other’s decisions about what method to use and the results of each method. So that ukhuwah Islam continues to run harmoniously.